Strategic Fight Against Terrorism: A Narrative of its Implication in the Sahel Region - Osaherumwen Idahosa, Stephen; Andreevich Degterev, Denis; Olasunkanmi Abidoye, Rasheed; ., . (International Journal of Engineering and Technology, 2018)
This paper explores the major impediments to peace and widespread interest in Sahel violence and stability. It examines the expansion of violent extremism across the Sahel and the direct consequence of unrest across North Africa. It assesses worrisome development in the regionâ€™s security landscape as these violent extremist organizations grow and develop sophisticated networks. It discovers that these emerging threats can be illustrated by the unique challenges facing Libya, Mali, Nigeria, and other countries in the region. Hence the strategies and assistance of Major Powers in ensuring the security and stability of the Sahel region, as it goes well beyond terrorism. Methodologically, it employs the use of descriptive analysis relying solely on secondary information for data generation and articulation. The study therefore suggests among others that, rather than attempt to stifle regional conflicts through military intervention, Major Powers should encourage regional initiatives. Many regional conflicts are so deeply rooted, however powers involve should recognize that, for there to be success in ending the fighting and instability, it should avoid policies that often clash with realities and needs on the ground, without which no outside party, from within or outside the region will succeed in putting an end to the threat to peace and security challenge.Â Â
Keywords: Instability Sahel; International cooperation; Intervention; Major Powers; NATO; Regional conflict.